2013
DOI: 10.1021/ja311463b
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Electron Transfer through a Hydrogen Bond between Single Molecules

Abstract: Understanding electron transfer (ET) from a single molecule to another single molecule holds essential importance to realize bottom-up molecular devices in which constituent molecules are self-assembled via noncovalent interactions between each other. However, rather little is currently known about the ET properties at the single-molecule interface. Here we employ molecular tips to quantify the ET through a H-bond between single molecules. We found that a H-bond conducts electrons better than a covalent σ bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
92
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 40 publications
(60 reference statements)
5
92
0
Order By: Relevance
“…Hence, we confirmed that water molecules can not only facilitate but also depress ET in peptides, being conditional ET. These observations are consistent with experimental results73. The low ET efficiency of peptides in aqueous solution is mainly due to unfavorable ET pathways.…”
Section: Resultssupporting
confidence: 93%
“…Hence, we confirmed that water molecules can not only facilitate but also depress ET in peptides, being conditional ET. These observations are consistent with experimental results73. The low ET efficiency of peptides in aqueous solution is mainly due to unfavorable ET pathways.…”
Section: Resultssupporting
confidence: 93%
“…MCBJ and I(s) experiments have shown that monothiolated OPE molecular wires can form π-stacking pairs in molecular junctions as long as the molecules are sufficiently long to facilitate strong enough aromatic stacking energetics (Figure 11a) (72,96). The second example is the formation of junctions through noncovalent hydrogen bonds between pairs of facing carboxylic acids (Figure 11b) (97). The third example shows the use of a fullerene molecular tip to facilitate assembly of a single noncovalently linked porphyrin-fullerene dyad (Figure 11c) (98).…”
Section: Supramolecular Interactions In Molecular Junctionsmentioning
confidence: 99%
“…7). 50 The STM tips were modified with SAMs of ω-carboxyl alkanethiols (HS(CH2)nCOOH, CnCOOH; Fig. 1(b), right for n = 2) to prepare the molecular tips, and a gold substrate was modified with CnCOOH.…”
Section: ·2 Electron Transfer Between Single Molecules Throughmentioning
confidence: 99%